Mid-term follow-up of non-ischemic heart preservation in heart transplantation - Jernryd, Victoria; Braun, Oscar; Paskevicius, Audrius; Metzsch, Carsten ; 0000-0003-1596-9562; Lofman, Ida Haugen; Ragnarsson, Sigurdur; Papageorgiou, Joanna Maria; Ingvarsson, Annika ; 0000-0003-1968-8880; Steen, Stig; Nilsson, Johan ; 0000-0001-6860-6090 (JHLT Open, 2025)
Background: Ex-vivo perfusion of donor hearts is gaining importance in minimizing ischemia-reperfusion injury during heart transplantation. The Non-Ischemic Heart Preservation (NIHP) device, developed in 2016, has shown promising results in pilot studies. This study aims to compare the mid-term follow-up outcomes of NIHP with traditional Static Cold Storage (SCS) in heart transplantation. Methods: This hybrid cohort study included 47 patients. The primary outcome was event-free survival at one year, defined as survival free of severe primary graft dysfunction (PGD), extracorporeal membrane oxygenation (ECMO) use within 7 days, acute cellular rejection (ACR ≥ 2R), and death. Secondary outcomes included graft function, incidence of adverse events at one year, and overall survival. Results: At 1 year, event-free survival was observed in 12 of 15 patients (80%) in the NIHP group and 23 of 32 patients (72%) in the SCS group. No patients in the NIHP group developed severe PGD, compared to three patients in the SCS group. ACR ≥ 2R occurred in 2/15 (13%) of NIHP patients and 5/32 (16%) of SCS patients. Overall survival at 5 years was 14/15 (93%) for NIHP and 24/32 (75%) for SCS. Immediate graft function and markers of ischemia-reperfusion injury favored the NIHP group, with lower CK-MB and lactate levels post-transplantation. Adverse events were comparable between groups, although the NIHP group had fewer severe complications. Conclusions: The NIHP system demonstrated outcomes comparable to SCS in heart transplantation, with improved graft function and reduced markers of ischemia-reperfusion injury. Further research is required to confirm these findings.
Keywords: Ex-vivo preservation; Heart transplantation; Ischemia; Primary graft dysfunction; Survival